Upaya Meningkatkan Keterampilan Membaca Siswa Kelas II SD Negeri 0104 Sibuhuan Dengan Menggunakan Alat Peraga Kartu Huruf - Siregar, Lailan Aprina; Hasibuan, Efrida Sofa; Siregar, Nurhayati (Journal Education Innovation (JEI), 2025)
The type of research used is classroom action research (PTK. The data collection technique in this research was obtained through observation and documentation. Based on the research results, it can be concluded that: (1) The reading skills of class II students at SD Negeri 0104 Sibuhuan in the pre-cycle were still low. This can be seen from the results of observations that have been made (2) The reading skills of class II students at SD Negeri 0104 Sibuhuan in cycle I have begun to improve. This can be seen from the results of observations that have been made in cycle I. The reading skills of students in the "Not Good" category are 1 students or as many 5%, the reading skills of students in the "Not Good" category are 8 students or as much as 40%, the reading skills of students in the "Good" category are 9 students or as much as 45% and the reading skills of students in the "Very Good" category are 2 students or as many as 10%. In cycle II increased quite significantly, there was 1 student's reading skills in the "Not Good" category or 5%, there were 3 students' reading skills in the "Not Good" category or 15%, students' reading skills in the "Not Good" category were 3 students or 15%. There were 14 students "Good" or 70% and the reading skills of students in the "Very Good" category were 2 students or 10%.